Cost‐effectiveness of induction of labour at term with a Foley catheter compared to vaginal prostaglandin E2 gel (PROBAAT trial). Issue 8 (26th March 2013) - van, GJ; Jozwiak, M; Opmeer, BC; Oude Rengerink, K; Benthem, M; Dijksterhuis, MGK; van, ME; van der, PCM; Schuitemaker, NWE; Papatsonis, DNM; Perquin, DAM; Porath, M; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the economic consequences of labour induction with Foley catheter compared to prostaglandin E2 gel. Design Economic evaluation alongside a randomised controlled trial. Setting Obstetric departments of one university and 11 teaching hospitals in the Netherlands. Population Women scheduled for labour induction with a singleton pregnancy in cephalic presentation at term, intact membranes and an unfavourable cervix; and without previous caesarean section. Methods Cost‐effectiveness analysis from a hospital perspective. Main outcome measures We estimated direct medical costs associated with healthcare utilisation from randomisation to 6 weeks postpartum. For caesarean section rate, and maternal and neonatal morbidity we calculated the incremental cost‐effectiveness ratios, which represent the costs to prevent one of these adverse outcomes. Results Mean costs per woman in the Foley catheter group (n = 411) and in the prostaglandin E2 gel group (n = 408), were €3297 versus €3075, respectively, with an average difference of €222 (95% confidence interval −€157 to €633). In the Foley catheter group we observed higher costs due to longer labour ward occupation and less cost related to induction material and neonatal admissions. Foley catheter induction showed a comparable caesarean section rate compared with prostaglandin induction, therefore the incremental cost‐effectiveness ratio was not informative. Foley induction resulted in fewer neonatal admissions (incremental cost‐effectiveness ratio €2708) and asphyxia/postpartum haemorrhage (incremental cost‐effectiveness ratios €5257) compared with prostaglandin induction. Conclusions Foley catheter and prostaglandin E2 labour induction generate comparable costs.